Characterization of Holmium-Doped Fiber Using AOM and Considering Pair-Induced Quenching and Fiber Length - Yuri Barmenkov; Pablo Muniz-Cánovas; José-Luis Cruz; Miguel V. Andrés (Photonics)
In this paper, we present the results of an experimental study on the characterization of holmium-doped silica fiber. A standard acousto-optic modulator controls the output power of the ytterbium-doped fiber laser operating at 1134.5 nm and serving as a pump source of the holmium-doped fiber under test. This technique allows us to measure the lifetimes of 5I7 and 5I8 energy levels of Ho3+ ions. The effects of the fiber length and the concentration-dependent pair-induced quenching on the accuracy of the fluorescence lifetime measurement are considered. The results of this study are compared with those obtained using the exponential and Förster decay functions used for such types of measurements. It is demonstrated that the knowledge of two fiber parameters, the pump saturation power and the fluorescence saturation power, together with the fiber absorption spectrum, permits one to obtain the absorption cross-sections at the pump and other key wavelengths, the effective concentration of the active ions, and the quantum efficiency of the fluorescence from the laser level. The results of this study are applicable to the reliable characterization of any type of heavily doped gain fibers and to the further numerical modeling and optimization of fiber lasers.